Kajian Fluktuasi Sifat Dielektrik Telur Puyuh yang Bervariasi pada Lama Penyimpanan - Irawan, Bagus; Maddu, Akhiruddin; Rustami, Erus; Sulaeman, Ahmad Sofyan; Putro, Permono Adi (TIME in Physics, 2024)
An increasing of public attention to the quality of food has been increasing, recently. One type of food that consumed is quail eggs (QE). In this study, QE were tested by Electrochemical Impedance Spectroscopy (EIS) method with some parameters such as complex impedance, dielectric constant, and loss tangent analysis. Several interesting results showed that dielectric properties of QE experience a fluctuation phenomenon if the test is influenced by storage duration, qualitatively. Therefore, we approximately prove that QE quality can be tested via EIS to obtain fine results.